MENINGKATKAN PRESTASI BELAJAR PAI MELALUI MODEL PEMBELAJARAN KOLABORASI - Atekan Atekan (MEDIA DIDAKTIKA, 2017)
The study was aimed to (1) describe the Islamic Education (PAI) learning process through collaborative learning model and (2) describes the learning achievement of PAI through collaborative learning model. The study was conducted at the sixth graders of state elementary school Weduni, Deket – Lamongan, which was designed to classroom action research (PTK) within three cycles. Each cycle was done through four stages: planning, implementation, observation, and reflection. The results showed that the students’ achievement has increased from cycle I to III, that was the first cycle (73.17%), Cycle II (82.93%), and the third cycle (95.12%). The results showed that the method of collaborative learning can improve Islamic education learning achievement.